“It’s Not the Same”: A Comparison of the Psychological Needs Satisfied by Musical Group Activities in Face to Face and Virtual Modes - Draper, Grace; Dingle, Genevieve A. (Frontiers in Psychology, 2021)
According to the social identity approach to health, group memberships influence people’s mental health to the extent that they identify with their group. Emerging evidence suggests that music groups such as choirs enhance mental health via group identification and the satisfaction of various psychological needs, however more research is required to understand these processes in other types of music groups. Furthermore, the COVID-19 social distancing restrictions in 2020 prevented music groups from meeting face to face (F2F). Some music groups adapted to virtual forms, but the rate of adaptation of various music activities is unknown, as is the impact of such adaptations on participants’ group identification, psychological need satisfaction, and mental health. We explored these questions using a cross-sectional survey with 257 participants (Mage = 46 years, 78% female) of singing (n = 172), instrumental (n = 48) and dance groups (n = 37). Participants rated group identification and psychological needs satisfaction retrospectively for their music group in F2F mode, and then for the group in adapted mode; along with mental health (SF-12). Results showed that instrumental groups (60%) were less commonly adapted to virtual mode than singing (83%) and dance (86%) groups. Group identification and average psychological needs satisfaction (M = 4.04 and 3.50 out of 5) scores were significantly lower for groups in virtual mode than in F2F mode (M = 4.53 and 4.14, respectively). Psychological needs satisfaction did not mediate the relationship between group identification and SF-12 mental health. Despite this, values on group identification and psychological need satisfaction remained high which suggests that virtual music groups may be beneficial during the COVID-19 pandemic and in contexts where F2F groups are less accessible.